Release and adoption of improved sweetpotato varieties in Southeast and South Asia - Gatto, M.; Hareau, Guy; Pradel, W.; Suarez, V.; Qin, J. (International Potato Center, 2018)
In this study we close the identified gaps in the existing literature and databases by documenting release and adoption of improved sweetpotato varieties in eight major sweetpotato producing countries in Southeast, South, and East Asia. Methodologically, this study adopts a refined expert elicitation (EE) approach applied in previous projects. EE workshops were used as an inexpensive alternative to the collection of national representative adoption data. An average of 12.67 experts working in the sweetpotato value chain participated in a one-day event to elicit perceived adoption rates and to update release databases. In total, 228 experts attended in 18 workshops held during 2014-2016.